Gut bacterial profiling of Malayan tapir (Tapirus indicus Desmarest) from Peninsular Malaysia using 16S rRNA metagenomics approach - Arumugam, Ramitha (2019)
Malayan tapir (Tapirus indicus) known as one of the endangered species listed by IUCN 2017. Less than 2,000 individuals recorded in the wild environment and the population is at alarming stage. According to field biologists, the main factors lead to tapir population decreasing is deforestation, habitat loss and illegal hunting. Currently, information such as diseases and genetic of Malayan tapirs are still lacking due to their inclusive characteristics and elusive as they lives in deep forest caused obstacles for researchers to collect their biological samples. Fresh invasive sample is required to obtain diseases related information but to collect biological samples of Malayan tapir are challenging due to time constraint, labor intensive and required an expertise. Thus, one of the approaches proposed in this thesis is by collecting faecal samples of tapirs from captivity and performed the study of gut bacteria profiling using metagenomics approach. Guts bacteria profiling acted as “second brain” in tapirs to determine their health condition. The aim of this study is to identify the bacteria profiling using 16S rRNA metagenomics on Illumina MiSeq platform to sequencing the high throughput sequences. Gut bacteria profiling were studied based on intrinsic factors where premeditated thru individual gut bacterial profiles and based on gender category; while extrinsic factors covered thru climate and types of enclosure variants. In nutshell, Firmicutes and Bacteriodetes were the dominant bacteria phyla founded in this study. Findings from this research has classified into shared bacteria taxanomy between the datasets and exclusively present in singular sub-dataset. From the putative result, we managed to visualised the overview and specific bacteria(s) presented in tapirs based on the intrinsic and extrinsic factors. Interestingly, individuals’ gut bacteria profiling were varying and some of the findings provides preliminary information to wildlife management to take precaution actions on the captivity conservation of Malayan tapir. Based on the obtained gut bacteria profiling results, few tapirs involves in this study were probed undergoing obesity, ulcer and vulnerable to water-borne diseases. However, further investigations require such in order to indorse the health condition of tapirs. Emphasizing here that metagenomics application acted as one of the advanced molecular tools only to provide putative bacteria taxonomy but not the meticulous tool to conclude the findings. Thus, other intense animal medical examination test(s) require crossing confirming the health condition of tapirs. The putative findings from this research can be applied as providing primary information to Peninsula wildlife management to diagnosis the diseases or screens the health condition of specific tapir(s), which prone to diseases based on this gut bacteria profile. As well, this study also acts as references for veterinarians to recognise and choose factual individual(s) for captive breeding programs and take care the welfare of the Malayan tapir.